Application and design of esterase-responsive nanoparticles for cancer therapy. (1st January 2019) - Dong, Haonan; Pang, Long; Cong, Hailin; Shen, Youqing; Yu, Bing
Abstract: Nanoparticles have been developed for tumor treatment due to the enhanced permeability and retention effects. However, lack of specific cancer cells selectivity results in low delivery efficiency and undesired side effects. In that case, the stimuli-responsive nanoparticles system designed for the specific structure and physicochemical properties of tumors have attracted more and more attention of researchers. Esterase-responsive nanoparticle system is widely used due to the overexpressed esterase in tumor cells. For a rational designed esterase-responsive nanoparticle, ester bonds and nanoparticle structures are the key characters. In this review, we overviewed the design of esterase-responsive nanoparticles, including ester bonds design and nano-structure design, and analyzed the fitness of each design for different application. In the end, the outlook of esterase-responsive nanoparticle is looking forward.